A montane species treeline is defined by both temperature and drought effects on growth season length. (23rd June 2022) - Bar-On, Peleg; Yaakobi, Assaf; Moran, Uri; Rozenstein, Offer; Kopler, Idan; Klein, Tamir
Abstract: Montane treelines are defined by a threshold low temperature. However, what are the dynamics when the snow-free summer growth season coincides with a 6-month seasonal drought? We tested this fundamental question by measuring tree growth and leaf activity across elevations in Mt Hermon (2814 m; in Israel and Syria), where oak trees ( Quercus look and Quercus boissieri ) form an observed treeline at 1900 m. While in theory, individuals can be established at higher elevations (minimum daily temperature >6.5 °C for >4 months even at the summit), soil drying and vapor pressure deficit in summer enforces growth cessation in August, leaving only 2–3 months for tree growth. At lower elevations, Q. look Kotschy is replaced by Quercus cerris L. (1300 m) and Quercus calliprinos Webb (1000 m) in accompanying Q. boissieri Reut., and growth season length (GSL) is longer due to an earlier start in April. Leaf gas exchange continues during autumn, but assimilates are no longer utilized in growth. Interestingly, the growth and activity of Q. boissieri were equivalent to that of each of the other three species across the ~1 km elevation gradient. A planting experiment at 2100 m showed that seedlings of the four oak species survived the cold winter and showed budding of leaves in summer, but wilted in August. Our unique mountain site in the Eastern Mediterranean introduces a new factor to the formation of treelines, involving a drought limitation on GSL. This site presents the elevation edge for each species and the southern distribution edge for both the endemic Q. look and the broad-range Q. cerris . With ongoing warming, Q. look and Q. boissieri are slowly expanding to higher elevations, while Q. cerris is at risk of future extirpation.